Employment and Innovations in the Environmental Sector: Determinants and Econometrical Results for Germany - Jens Horbach (Fondazione Eni Enrico Mattei (FEEM), 2003)
Besides other determinants environmental regulation, institutions like environmental agencies and social customs lead to a demand for environmental goods and services. On the basis of the public choice theory it can be shown that environmental regulation is endogenous and can be influenced by the environmental awareness of voters and interest groups. Following the so-called Porter hypothesis early developed environmental legislation induces environmental innovations and creates first mover advantages connected with a high international competitiveness of the environmental industry. An empirical analysis based on the establishment panel of the Institute for Employment Research (IAB) shows that more than 900,000 persons are employed in the environmental sector in Germany. Following the results of an econometrical analysis of employment perspectives and innovation behaviour integrated environmental technologies will become more relevant whereas employment in traditional end-of-pipe fields like the prevention of waste water pollution or air pollution will be reduced.
Keywords: Q21; J4; C25; 330; Employment; Environmental sector; Innovation behaviour; Umweltwirtschaft; Erwerbstätigkeit; Innovation; Deutschland